Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Komitmen Kerja Pegawai Pada Bank Muamalat KCU Makassar - Gibrannisa D. Azzury; Tenri S.P. Dipoatmodjo; Uhud Darmawan Natsir; Romansyah Sahabuddin; Rezky Amalia Hamka (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to (1) determine whether the work environment partially has a positive effect on employee work commitment at Bank Muamalat KCU Makassar, (2) Knowing compensation partially has a positive effect on employee work commitment at Bank Muamalat KCU Makassar, and (3) Knowing whether the work environment and compensation simultaneously have a positive effect on employee work commitment at Bank Muamalat KCU Makassar. The population at Bank Muamalat KCU Makassar was 87 employees in 2023. The number of samples in this study was 87 people, because all employees were used as respondents or research subjects. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using Statistical Product Servive Solution (SPSS). The results showed that: 1) The work environment variable partially does not have a positive and insignificant physical influence on the work commitment of Bank Muamalat KCU Makassar employees, 2) Non-physical work environment variables partially have a positive and significant influence on employee work commitment at Bank Muamalat KCU Makassar, 3) Financial compensation variables partially have a positive and significant influence on employee work commitment at Bank Muamalat KCU Makassar, 4) Non-financial compensation variables partially have a positive and significant influence on employee work commitment at Bank Muamalat KCU Makassar, and 5) Work environment variables and compensation simultaneously have a positive and significant influence on employee work commitment at Bank Muamalat KCU Makassar.